Distributed systems : concepts and design. - Coulouris, George, ....-; Dollimore, Jean, ....-; Kindberg, Tim, ....- (Harlow : Addison-Wesley, 2009)
From mobile phones to the Internet, our lives depend increasingly on distributed systems linking computers and other devices together in a seamless and transparent way. The fourth edition of this best-selling text continues to provide a comprehensive source of material on the principles and practice of distributed computer systems and the exciting new developments based on them, using a wealth of modern case studies to illustrate their design and development.